Chromosome studies on the silky anteater Cyclopes Didactylus L. (Myrmecophagidae: Xenarthra, Edentata) - Jorge, Wilham; Best, Robin C. [UNESP]; Wetzel, Ralph M. (My University, 1985)
The karyotype of the silky anteater Cyclopes didactylus, the smallest of the anteaters is described. A notable difference in karyotypes exists between C. didactylus (2n = 64) and the other species of the family Myrmecophagidae. Both fusion/fission as well as other mechanisms are probably involved in the reduction of the chromosome number of 64 chromosome in Cyclopes to 60 and 54 in Tamandua and Myrmecophaga, respectively. © 1985 Taylor & Francis Group, LLC.